The Relationship Between the Duration of Device Use and the Cognitive Development of 6 Year Old Children at Sukaraya 04 State Elementary School in 2024 - Marini Iskandar; Syifa Halida Kamila (Journal of Educational Innovation and Public Health, 2025)
The high level of internet access among children aged 5 years and over in Indonesia with a percentage of 12.43%, the 3rd highest in the classification of internet use based on age after those aged 25 years and over in first place and those aged 19-24 years in second place. This research aims to determine the relationship between the duration of device use and cognitive development in 6 year old children at SDN Sukaraya 04 in 2024. This research design uses a cross-section technique with the entire population of 82 6 year old students at SDN Sukaraya 04 and their parents. the. The sampling technique was a total sampling of 82 students. Data were collected using primary data by distributing questionnaires with data analysis using univariate analysis and bivariate analysis using the chi square test. Based on the research results, it shows that there is a relationship between the duration of device use and the cognitive development of 6 year old children at SDN Sukaraya 04 in 2024 with a statistical p value of 0.002 (a<0.05) and the OR result was 6.026. Based on the research results, 21 respondents (47.7%) who used devices in the risk category experienced poor cognitive development. It is hoped that this research can be a guide for parents to pay more attention to the duration of device use for children aged 6 years so as not to interfere with cognitive development.